Cadastral system migration from deeds registration to titles registration: case study of Sri Lanka. Issue 330 (1st May 2013) - Divithure, H; Tang, C
<x xml:space="preserve">Abstract</x> Sri Lanka has two types of cadastral system operating in the country and is in the process of cadastral system migration from deeds registration to titles registration. The deeds system, which was introduced in 1863, is well established, and the titles registration system, the introduction of which is ongoing, was initiated in 1998. Expectedly, the deeds system has several drawbacks, while the titles system meets unexpected difficulties. The purpose of this paper is to give an overview and a comparative analysis of both systems, thereby suggesting options for improvement.